A Prospective, Randomized, Double-Blinded Study of the Effect of Intravenous Ondansetron on the Effective Dose in 50% of Subjects of Prophylactic Phenylephrine Infusions for Preventing Spinal Anesthesia-Induced Hypotension During Cesarean Delivery - Xiao, Fei; Wei, Changna; Chang, Xiangyang; Zhang, Yinfa; Xue, Lili; Shen, Huaxiang; Ngan Kee, Warwick D; Chen, Xinzhong (Anesthesia and analgesia, 2020)
Ondansetron has been shown to reduce the incidence of hypotension and vasopressor requirement during spinal anesthesia for obstetric and nonobstetric surgery. However, the magnitude of this effect has not been fully quantified. In this parallel-group, randomized, double-blinded study, we determined the effective dose in 50% of subjects (ED50) of a prophylactic phenylephrine infusion for preventing hypotension in patients who received a single dose of intravenous ondansetron 4 mg or saline control before combined spinal-epidural anesthesia for elective cesarean delivery. ED50 values obtained were compared to estimate the effect of ondansetron versus placebo on vasopressor requirement. Sixty parturients were randomly assigned to receive ondansetron (group O) or saline control (group C) 10 minutes before positioning for induction of spinal anesthesia. A prophylactic phenylephrine infusion was used to prevent hypotension. The first patient in each group received a phenylephrine infusion at the rate of 0.5 µg/kg/min. The infusion rate for each subsequent patient was varied with increments or decrements of 0.05 µg/kg/min based on the response of the previous patient, and the effective dose of the phenylephrine infusion for preventing hypotension in 50% of patients (ED50) was calculated for each group and compared using up-down sequential analysis. Probit regression was applied as a backup and sensitivity analysis was used to compare ED50 values for phenylephrine between groups by comparing calculated relative mean potency. The ED50 (mean [95% confidence interval (CI)]) of the rate of phenylephrine infusion was lower in group O (0.24 µg/kg/min [0.10-0.38 µg/kg/min]) compared with group C (0.32 µg/kg/min [0.14-0.47 µg/kg/min]) (P < .001). The total consumption of phenylephrine (mean ± standard deviation [SD]) until delivery was lower in group O (316.5 ± 25.9 µg) than in group C (387.7 ± 14.7 µg, P = .02). The estimate of relative median potency for phenylephrine for group O versus group C was 0.74 (95% CI, 0.37-0.95). Under the conditions of this study, intravenous ondansetron 4 mg reduced the ED50 of a prophylactic phenylephrine infusion by approximately 26% in patients undergoing cesarean delivery under combined spinal-epidural anesthesia.